Development of loop-mediated isothermal amplification (LAMP) assays for the rapid detection of allergic peanut in processed food. (15th August 2018) - Sheu, Shyang-Chwen; Tsou, Po-Chuan; Lien, Yi-Yang; Lee, Meng-Shiou
Highlights: A high specificity LAMP primer for the detection of peanut was developed. The detection limit of LAMP was more sensitive than PCR. No cross-reactivity of LAMP was evident when peanut was mixed with other nut ingredients. Various processed foods containing peanut were identified by LAMP. Raw peanut and commercial foods containing peanut can be identified. Abstract: Peanut is a widely and common used in many cuisines around the world. However, peanut is also one of the most important food allergen for causing anaphylactic reaction. To prevent allergic reaction, the best way is to avoid the food allergen or food containing allergic ingredient such as peanut before food consuming. Thus, to efficient and precisely detect the allergic ingredient, peanut or related product, is essential and required for maintain consumer's health or their interest. In this study, a loop-mediated isothermal amplification (LAMP) assay was developed for the detection of allergic peanut using specifically designed primer sets. Two sets of the specific LAMP primers respectively targeted the internal transcribed sequence 1 (ITS1) of nuclear ribosomal DNA sequence regions and the ara h1 gene sequence of Arachia hypogeae (peanut) were used to address the application of LAMP for detecting peanut in processed food or diet. The results demonstrated that the identification of peanut using the newly designed primers for ITS 1 sequence is more sensitive rather than primers for sequence of Ara h1 gene when performing LAMP assay. Besides, the sensitivity of LAMP for detecting peanut is also higher than the traditional PCR method. These LAMP primers sets showed high specificity for the identification of the peanut and had no cross-reaction to other species of nut including walnut, hazelnut, almonds, cashew and macadamia nut. Moreover, when minimal 0.1% peanuts were mixed with other nuts ingredients at different ratios, no any cross-reactivity was evident during performing LAMP. Finally, genomic DNAs extracted from boiled and steamed peanut were used as templates; the detection of peanut by LAMP was not affected and reproducible. As to this established LAMP herein, not only can peanut ingredients be detected but commercial foods containing peanut can also be identified. This assay will be useful and potential for the rapid detection of peanut in practical food markets.